OPTIMALISASI PEMANFAATAN ASET TANAH DALAM MENINGKATKAN PENDAPATAN DAERAH: TINJAUAN EKONOMI - Loso Judijanto (BORJUIS: JURNAL OF ECONOMY, 2025)
This study discusses the optimisation of land asset utilisation by local governments as a strategic effort to increase local revenue (PAD) from an economic perspective. Using a literature review method, this study examines the concepts, theories, and practices of effective and efficient land asset management, including supporting factors and obstacles encountered in its implementation. The findings indicate that planned, transparent land asset management that leverages information technology can increase the economic value of land and local revenue in a sustainable manner. Additionally, the role of public-private partnerships and adaptive regulations are key to successfully optimising land assets. This study provides policy recommendations that can serve as a basis for local governments in developing innovative and accountable land asset management mechanisms to promote economic growth and community welfare.